Cancer cachexia and myopenia – Update on management strategies and the direction of future research for optimizing body composition in cancer – A narrative review. (November 2018) - Pring, Edward T.; Malietzis, George; Kennedy, Robin H.; Athanasiou, Thanos; Jenkins, John T.
Highlights: Myopenia is recognized as an independent predictor of poorer outcomes in cancer. Preservation of muscle mass and quality could improve outcomes in cancer. Multiple approaches have been explored in order to modify body composition and preserve muscle mass and quality but with no single modality has been proven to have been successful to date. Multidisciplinary and multimodal therapies are discussed in this review are likely to be key in managing this complex syndrome in the future. Abstract: Purpose: Body composition degenerates with cancer. Optimizing body composition is rarely, if ever, undertaken. This narrative review highlights and evaluates emerging treatments that have the potential to improve outcomes for our cancer patients. Observations: Body composition in cancer patients has been shown to be modifiable; enhanced body composition is associated with improved short term, long-term outcomes and survival in addition to improvements in function and quality of life. Conclusions and relevance: A multimodal approach to body composition optimization formulated by a multidisciplinary team in a patient-centric manner can improve outcome. As part of a multifaceted approach to patient treatment, body composition modification should be considered to expand our armoury in fighting the systemic burden of cancer.